2007
DOI: 10.1016/j.radonc.2007.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the in vivo radiosensitivity of human skin fibroblasts

Abstract: Background and Purpose-To examine the radiosensitivity of skin cells obtained directly from the irradiated skin of patients undergoing fractionated radiation treatment prior to surgery for treatment of soft tissue sarcoma (STS) and to determine if there was a relationship with the development of wound healing complications associated with the surgery post-radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…These doses were also chosen to cover a range approximately equivalent to the fractionated treatment received by human skin in our previous study (1). The animals were irradiated at 9 weeks of age, and we assayed the skin 1 day or 2 months after irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These doses were also chosen to cover a range approximately equivalent to the fractionated treatment received by human skin in our previous study (1). The animals were irradiated at 9 weeks of age, and we assayed the skin 1 day or 2 months after irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The animals were irradiated at 9 weeks of age, and we assayed the skin 1 day or 2 months after irradiation. These times were chosen based on our previous studies in lung (1 day) and in human skin (1), where it represents the approximate time at which most of the skin specimens were analyzed relative to the end of the course of fractionated radiation treatment. The results of these studies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiosensitivity in different cell types is a limiting factor for use of radiotherapy in many clinical complications including cancers [28][29][30] . Therefore, much interest in normal tissue response to ionizing radiation has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…For example, micronuclei in skin fibroblasts are dependent on radiation dose (34). Cytogenetic analysis using skinpunch biopsies at various locations can define the extent of local radiation exposure.…”
Section: Cutaneous Bioindicators and Medical Managementmentioning
confidence: 99%